The youngest ophiocistioid: a first Palaeozoic‐type echinoderm group representative from the Mesozoic. (27th July 2018) - Reich, Mike; Stegemann, Tanja R.; Hausmann, Imelda M.; Roden, Vanessa J.; Nützel, Alexander
Abstract: Articulated ophiocistioids are rare as fossils, enigmatic in terms of their phylogenetic position, and have been considered to be an exclusively Palaeozoic echinoderm group. Apart from articulated body fossils, the fossil record of Ophiocistioidea is otherwise dependent on isolated microfossils. However, it has been demonstrated that disarticulated jaw elements (goniodonts) of ophiocistioids can be diagnostic at genus and species level and can be used to fill gaps in the non‐articulated fossil record. The Late Triassic Cassian Formation of Italy is regarded as one of the most important strata of early Mesozoic invertebrates worldwide. A fossil assemblage from a locality near Misurina, South Tyrol, yielded various echinoderms, including a stem group echinoid representative and a new ophiocistioid, Linguaserra triassica sp. nov. The new taxon is described and placed within linguaserrid ophiocistioids. The evolutionary history of the group is briefly discussed in relation to other taxa of the Ophiocistioidea and Echinoidea. Linguaserra triassica not only represents the first documented occurrence of this 'Palaeozoic' echinoderm class from Mesozoic strata but also establishes the stratigraphically youngest record of goniodonts or ophiocistioid teeth in the world.